Saylor, Alexander and Lewis’s Curriculum Development Model for Islamic Education in Schools - Mardhiyah Taufik; Endis Firdaus (Perhimpunan Intelektual Muslim Indonesia, 2021)
This study aims to identify the curriculum development model by Saylor, Alexander, and Lewis for Islamic education and its implications in schools. This study applied qualitative approach and literature study methods. The results of this study indicate that the curriculum is in line with the times. The curriculum also develops to meet the demands of current education systems. To achieve a goal in the educational process requires a design in implementation. Therefore, the curriculum is a design in which there are systematically designed programs to set a goal. Saylor, Alexander, and Lewis consider curriculum as the efforts of schools to influence students to learn, both in the classroom, on the schoolyard, and outside the school. Therefore, there are various demands that Islamic education must be able to answer those needs. Islamic Education is a vast subject in schools. It needs to be selected for its material and developed according to the needs and competencies of students and has use of value for students. Systematically, this paper implies that it tries to provide an overview of the Saylor, Alexander, and Lewis curriculum models and can guide carrying out activities and their implementation in Islamic education.